Numerical investigation on the hydraulic parameters’ effects on the circular-crested weir - Mahdi Majedi-Asl; Hadi Arvanaghi; Mehdi Fuladipanah; Omid Ghasemzadeh; Tohid Omidpour Alavian (Journal of Hydraulic Structures)
A paramount determinant in the selection of irrigation canal overflow configurations resides in their flow conveyance capacity. This overflow capacity is contingent upon the effective length and geometric characteristics of the weir. In the present investigation, the hydraulic performance and discharge coefficient (Cd) of circular-crested weir were scrutinized through the utilization of FLUENT software. Specifically, the study delved into the impact of geometric parameters, namely the radius and height of the crest, on these hydraulic aspects. Following the execution of calibration and validation procedures using FLUENT in conjunction with laboratory-derived data, the outcomes of the simulation revealed that augmenting the radius of the crest led to a corresponding escalation of 144.28% in the maximum pressure exerted on the crest and a 6.84% increase in flow depth. Conversely, the maximum velocity and Cd experienced reductions of 6.84% and 7.82%, respectively. The elevation of the weir height exhibited negligible influence on the maximum pressure magnitude at the crest. Contrastingly, a reduction in weir height constricted the range of pressure variations on the crest, indicating a more limited domain of pressure changes. Elevating the weir height induces a notable augmentation in the maximum flow velocity at the crest by 44.36%, concomitant with a reduction in both the depth and Cd by 52.66% and 68.96%, respectively.